Comparative analysis of the influence of solar radiation screen ageing on temperature measurements by means of weather stations. (26th June 2013) - Lopardo, G.; Bertiglia, F.; Curci, S.; Roggero, G.; Merlone, A.
Abstract Solar radiation screens play a key role in automatic weather stations (AWS) performances. In this work, screen ageing effects on temperature measurements are examined. Paired temperature observations, traceable to national standards and with a well‐defined uncertainty budget, were performed employing two naturally ventilated weather stations equipped with identical sensors and different only for their working time. Three different tests were carried out employing different aged AWSs: a 5‐year‐old AWS (AWS5) was compared with a new device (AWS0), a 1 year old (AWS1) was compared with both a 3 years old (AWS3) and a new one devices (AWS00). Due to solar and weather conditions exposure a degradation of the screen reflective coating is evident for the older AWSs (5 and 3 years old) and so a qualitative estimation of how different conditions of ageing affect the temperature drift was done. During the comparison 0 to 5 and 1 to 3‐year‐old screens, significant temperature differences were recorded at different times of the day. The differences, wider than the uncertainty amplitude, demonstrate a systematic effect. The temperature measured with the older screen is larger, and the maximum instantaneous difference was 1.63 °C (for 0–5 years comparison) in daytime hours. During night‐time the two AWS's measure the same temperature (within the uncertainty amplitude). This behaviour, increasing with increasing solar radiation intensity and decreasing with increasing wind speed, is attributed to a radiative heating effect. The screen ageing has compromised the shield effectiveness introducing a significant change in the temperature evaluation. The experimental results of a further comparison, between 0‐ and 1‐year‐old screens, confirm the same conclusion showing a negligible ageing effect, within the uncertainty amplitude.